Pemanfaatan dan Konservasi Keanekaragaman Sumber Daya Genetik Tanaman Pangan di Lahan Pekarangan - Sutoro Sutoro (Iptek Tanaman Pangan, 2017)
Traditional food crops have been cultivated in the home garden of rural communities since long times ago. The type of food crops to be grown is influenced by preferences of the owners of home garden, land area, agroclimate, and socio-economic as well as the culture of the local community. Food crops producing carbohydrates and protein grown at the home gardens are functioning to supply the daily needs and as food reserves for longer term. The type and number of crops grown at the home garden vary greatly among farmers and regions, resulting a rich food crop genetic resource reserved. Each individual farmer retains local strains and varieties, derived from previous season and from their ancestors, so it serves as in situ conservation or as the on-farm genetic resources preservation. The diversity of plant genetic resources conserved in the on-farm has shifted considerably, especially in the near urban communities, from traditional food crops to more commercial crops. But in the remote villages, diverse food crop genetic resources are still maintained. The on-farm conservation of food crop genetic resources along with their direct utilization for food by farmers, should be improved of their cultivation, harvesting and processing techniques so that it will increase the added value of the crops. This way, it would facilitate the sustainability of the conservation of food crop genetic resources.